fine the limits-without-lhopital rule and Taylor series :

$$\lim_{x \to 0} \frac{(\sin 2x-2x\cos x)(\tan 6x+\tan(\frac{\pi}{3}-2x)-\tan(\frac{\pi}{3}+4x))}{x\sin x \tan x\sin 2x}=?$$

i know that :

$$\lim_{x \to 0} \frac{\sin x}{x}=1=\lim_{x \to 0}\frac{\tan x}{x}$$

But I can not answer please help .

  • $\begingroup$ any thoughts by yourself? $\endgroup$ – Arnaldo May 17 '17 at 13:14
  • $\begingroup$ @Arnaldo .$\tan 6x+\tan(\frac{\pi}{3}-2x)-\tan(\frac{\pi}{3}+4x))=\tan 6x-\cot(\frac{\pi}{6}-4x)+\cot(\frac{\pi}{6}+2x))$ now ? $\endgroup$ – Almot1960 May 17 '17 at 13:18
  • $\begingroup$ I believe the answer should be approximately 2.33 $\endgroup$ – John Lou May 17 '17 at 13:20
  • $\begingroup$ If you can solve $\lim_{x\to 0}\frac{1}{x^2}(1-\frac{\sin x}{x})$ (with allowed methods) than I will show you the (elementary) rest. :-) $\endgroup$ – user90369 May 17 '17 at 14:29
  • $\begingroup$ @user90369 . how ? please write $\endgroup$ – Almot1960 May 17 '17 at 14:36

If you know, that $\enspace\displaystyle \lim\limits_{x\to 0}\frac{1}{x^2}(1-\frac{\sin x}{x})=\frac{1}{3!}\enspace$ then you can answer your question easily:

$\displaystyle \frac{(\sin(2x)-2x\cos x)(\tan(6x)+\tan(\frac{\pi}{3}-2x)-\tan(\frac{\pi}{3}+4x))}{x\sin x\tan x\sin(2x)}=$

$\displaystyle =\frac{(\sin(2x)-2x\cos x)(\frac{\sin(6x)}{\cos(6x)}-\frac{\sin(6x)}{\cos(\frac{\pi}{3}-2x)\cos(\frac{\pi}{3}+4x)})}{x\sin x\tan x\sin(2x)}$

$\displaystyle =\frac{2\sin x\cos x -2x\cos x}{\sin x\tan x\sin(2x)}6\frac{\sin(6x)}{6x}(\frac{1}{\cos(6x)}-\frac{1}{\cos(\frac{\pi}{3}-2x)\cos(\frac{\pi}{3}+4x)})$

$\displaystyle =-\frac{1}{x^2}(1-\frac{\sin x}{x}) (\frac{x}{\sin x}\cos x)^2 \frac{2x}{\sin(2x)} 6\frac{\sin(6x)}{6x}(\frac{1}{\cos(6x)}-\frac{1}{\cos(\frac{\pi}{3}-2x)\cos(\frac{\pi}{3}+4x)})$

$\displaystyle \to -\frac{1}{3!}6(1-4)=3\enspace$ for $\enspace x\to 0$

A note about what I have used:

$\displaystyle \tan x=\frac{\sin x}{\cos x}$

$\sin(2x)=2\sin x\cos x$

$\displaystyle \tan x-\tan y=\frac{\sin(x-y)}{\cos x\cos y}$


Here is a different way.

You can use standard Taylor series expansions, as $x \to 0$, to get $$\sin 2x-2x\cos x=-\frac{x^3}3+o(x^4) $$ $$\tan 6x+\tan(\frac{\pi}{3}-2x)-\tan(\frac{\pi}{3}+4x))=-18x+o(x^2) $$ $$x\sin x \tan x\sin 2x=2x^4+o(x^5)$$ then $$\lim_{x \to 0} \frac{(\sin 2x-2x\cos x)(\tan 6x+\tan(\frac{\pi}{3}-2x)-\tan(\frac{\pi}{3}+4x))}{x\sin x \tan x\sin 2x}=\lim_{x \to 0}\frac{\frac{18}{3}x^4+o(x^5)}{2x^4+o(x^5)}=3. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.